1986
DOI: 10.1051/rnd:19860507
|View full text |Cite
|
Sign up to set email alerts
|

Uterine motor responses to an α-adrenergic agonist (phenylephrine) in the ewe during oestrus and at the end of gestation

Abstract: Summary. The a-adrenergic activity of the myometrium was studied by recording the electromyographic activity (EMG) of the uterus in 4 conscious cyclic ewes during oestrus and in 8 conscious pregnant ewes during the last 6 days of gestation.In the cyclic ewes, changes in intra-uterine pressure were recorded at the same time as the EMG. Motor responses to perfusions of phenylephrine, a specific a-adrenergic agonist, were studied at three uterine sites. In the ewes in oestrus, uterine activity was stimulated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The uterine contractile responses to these neurotransmitters have been studied widely, mostly in vitro, in various experimental animal species [3,10,14,19,25,26,[31][32][33] as well as in humans [4,7,8,34]; considerable information about the mechanism or mechanisms by which these neurotransmitters stimulate contraction has been gathered. With respect to the contractile response of the uterus to cholinomimetics, many studies have indicated the existence of abundant muscarinic receptors in the uterine smooth muscle [3,4,7,8,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uterine contractile responses to these neurotransmitters have been studied widely, mostly in vitro, in various experimental animal species [3,10,14,19,25,26,[31][32][33] as well as in humans [4,7,8,34]; considerable information about the mechanism or mechanisms by which these neurotransmitters stimulate contraction has been gathered. With respect to the contractile response of the uterus to cholinomimetics, many studies have indicated the existence of abundant muscarinic receptors in the uterine smooth muscle [3,4,7,8,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to other adrenergic receptors, phenylephrine (atl agonist) [13,14,25], clonidine (at2 agonist) [13], and butoxamine (2 antagonist) were found to enhance uterine spontaneous contractile activity, whereas prazosin (a 1 antagonist) [10], yohimbine (a 2 antagonist) [10], dobutamine (1 agonist), and atenolol ([3 antagonist) did not influence the spontaneous contractions at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It activates nrreceptors of the adrenergic system (Savo/a 1986, Salonen 1986, Virtanen 1986. Previous information indicates that the a-receptor agonist xylazine and phenylephrine induce uterine contractions in cows and ewes (Le Bfac et al 1984, Prudhomme 1986. Thus the use of n-agonists during pregnancy can create the risk of abortion.…”
Section: Introductionmentioning
confidence: 99%